Overarching Unified theory of acceptance and use of technology (UTAUT) model on the factors effecting behavioral intention towards e-government adoption in Malaysia - Azidin, Siti Sarah; Romle, Abd Rahim; Mansor, Mohd Hafiz (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
As one of the strategies to achieve Vision 2020, Multimedia Super Corridor (MSC) had been introduced as an initiative to develop Malaysia towards the new Information Age.The e-Government initiative was introduced in Malaysia by the former Malaysian Prime Minister, Tun Dr Mahathir Mohamad on 24 February 2004.With this e-government implementation, it will unquestionably benefit the citizens to access the various government services conveniently at any place any time.However, relatively little known about the adoption of e-government among citizens specifically at the sub urban area in Malaysia.Thus, this research is intended to explore the key factors that influence the intentional behavior to use e-government applications based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model.